Flow and Self-Presentation in Runners Participating in 5 and 10 Kilometer Road Races - Amanda E. Edwards; Robert C. Eklund (Pamukkale University, 2011)
The purpose of this investigation is to explore the relationship between flow state and self-presentation in runners. It was hypothesized that Self-presentation will be negatively and moderately correlated with the flow experience.A questionnaire packet containing an informed consent form, a demographic information handout, a Race Flow Scale (Modified DFS-2; Jackson & Eklund, 2002), and the Modified Self-Presentation in Sport Questionnaire (SPSQ; McGowan et al., 2008) was administered to 210 male and female runners. The analyses of this investigation are presented in two subsections: descriptive statistics and correlational analyses (including the results of a canonical correlation). It was found that individuals who experience self-presentational concerns are less likely to attain the state of flow. Implications and future research directions are discussed.